The impact of chronic kidney disease on developed countries from a health economics perspective: A systematic scoping review. - Sarah Elshahat; Paul Cockwell; Alexander P Maxwell; Matthew Griffin; Timothy O'Brien; Ciaran O'Neill (PLoS ONE)
Chronic kidney disease (CKD) affects over 10% of the global population and poses significant challenges for societies and health care systems worldwide. To illustrate these challenges and inform cost-effectiveness analyses, we undertook a comprehensive systematic scoping review that explored costs, health-related quality of life (HRQoL) and life expectancy (LE) amongst individuals with CKD. Costs were examined from a health system and societal perspective, and HRQoL was assessed from a societal and patient perspective. Papers published in English from 2015 onward found through a systematic search strategy formed the basis of the review. All costs were adjusted for inflation and expressed in US$ after correcting for purchasing power parity. From the health system perspective, progression from CKD stages 1-2 to CKD stages 3a-3b was associated with a 1.1-1.7 fold increase in per patient mean annual health care cost. The progression from CKD stage 3 to CKD stages 4-5 was associated with a 1.3-4.2 fold increase in costs, with the highest costs associated with end-stage renal disease at $20,110 to $100,593 per patient. Mean EuroQol-5D index scores ranged from 0.80 to 0.86 for CKD stages 1-3, and decreased to 0.73-0.79 for CKD stages 4-5. For treatment with renal replacement therapy, transplant recipients incurred lower costs and demonstrated higher HRQoL scores with longer LE compared to dialysis patients. The study has provided a comprehensive updated overview of the burden associated with different CKD stages and renal replacement therapy modalities across developed countries. These data will be useful for the assessment of new renal services/therapies in terms of cost-effectiveness.